Standardisasi Ekstrak Etanol Umbi Tawas Ut (Ampelocissus rubiginosa Lauterb.) asal Kalimantan Tengah - Nurul Qamariah; Rezqi Handayani; Reni Wulandari (Jurnal Surya Medika (JSM), 2019)
Standardization is the process of ensuring that the final product of the drug has a good quality value based on certain parameters that have been set. The purpose of this study was to describe the standardization of the ethanol extract of Tawas Ut tuber (Ampelocissus rubiginosa Lauterb.) From Central Kalimantan. This study uses a descriptive method with a laboratory approach that is divided into two parameters, namely specific and non-specific parameters. Specific parameters include extract identity, organoleptic examination and identification of chemical compounds, and non-specific parameters including total ash content, acid insoluble ash, specific gravity and microbial contamination. The results of specific standardization parameters, from the identity of the extract, obtained the name of the extract, the ethanol extract of Ut Tawas tuber, the Latin name of the plant (Ampelocissus rubiginosa Lauterb.), the plant parts used are tuber, and the Indonesian name of the plant is Tawas Ut, dark red, odourless and bitter and chelate taste, identification of chemical compounds showed that the extract positively contained alkaloids, flavonoids, saponins, and tannins. The results of non specific extract standardization parameters showed total ash content of 0.61 ± 10-4, acid insoluble ash content of 0.17% ± 10-3, density of 0.9151 mass/ volume ± 6x10-4, and testing microbial contamination, number of moulds and yeast there is no contamination which means the extract is not polluted and has fulfilled the requirements.